51.2k views
3 votes
3(x-4) = 2 (-2x + 1)

User Nserror
by
5.8k points

1 Answer

3 votes

Answer:

I believe x = 2.

Use distributive prop. to get rid of parentheses:

3x-12=-4x+2

Move the -12 over to the other side. Since everything that goes to the other side changes signs, the "-" sign will change to a "+" sign. Move the -4x to the other side as well. Remember to change the sign!

3x + 4x = 2 + 12

Now combine like terms:

7x = 14

To get the x fully isolated, we need to divide both sides by 7 so we can get rid of the 7.

7x/7 = 14/7

x = 2

Hope this helped! :)

User Jefrey
by
4.2k points